The effect of adenoid hypertrophy on growth-development level and dental maturation: a 15-year retrospective radiographs study - Elif Merve Ahlat; Fahinur Ertuğrul; Bülent Baydaş; Nazan Ersin; Behrang Ghabchi (BMC Oral Health)
Abstract Background This study aimed to retrospectively evaluate the effect of adenoid hypertrophy on growth development levels and dental age in pediatric patients aged 7–12 years, using panoramic and lateral cephalometric radiographs. Methods This analytical-archival study assessed radiographs of 348 children aged 7–12 who underwent orthodontic examination at a private oral and dental health polyclinic between 2008 and 2023. Dental ages were estimated using the Nolla methods based on panoramic radiographs. Lateral cephalometric radiographs were analyzed using the Webceph™ program. Adenoid hypertrophy was assessed with the McNamara Method, while growth development levels were evaluated using the Baccetti Cervical Vertebral Maturation (CVM) stages. Results Adenoid hypertrophy was identified in 29.8% of the patients (n = 348). SNA, SNB, ramus height, and face height ratio values were significantly higher in the control group (P < 0.05). FMA, SN-GoMe, mandibular plane angle, and Y-axis angle values were significantly higher in the study group (P < 0.05). No significant differences were found for ANB, gonial angle, lower gonial angle, or convexity angle (P > 0.05). In CS1 and CS3 stages, boys had significantly higher chronological ages than girls (P < 0.05), while no gender-based differences were observed in CS2 and CS4 stages (P > 0.05). The Baccetti classification stages increased with age in both genders, with a statistically higher rate of increase in girls (P < 0.05). However, no significant differences were found in chronological age between study groups within the same Baccetti stages (P > 0.05). Nolla ages were significantly lower in the study group (P < 0.05). Conclusion Adenoid hypertrophy did not significantly affect growth development levels based on cervical vertebral maturation in children aged 7–12. However, Nolla dental ages were significantly delayed in patients with adenoid hypertrophy, suggesting a negative impact on tooth eruption and development. A multidisciplinary approach involving pediatric dentists, orthodontists, ENT specialists, and pediatricians is essential to address the effects of respiratory disorders.